2007
DOI: 10.1016/j.taap.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

2,2′,4,4′-Tetrachlorobiphenyl upregulates cyclooxygenase-2 in HL-60 cells via p38 mitogen-activated protein kinase and NF-κB

Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous, persistent environmental contaminants that affect a number of cellular systems, including neutrophils. Among the effects caused by the noncoplanar PCB 2,2′,4,4′,-tetrachlorobiphenyl (2244-TCB) in granulocytic HL-60 cells are increases in superoxide anion production, activation of phospholipase A 2 with subsequent release of arachidonic acid (AA), and upregulation of the inflammatory gene cyclooxygenase-2 (COX-2). The objective of this study was to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
(73 reference statements)
2
6
0
Order By: Relevance
“…To support this notion, our results also indicate an increased superoxide production in PCB153-exposed hCMEC/D3 cells. These observations are supported by recent reports that selected ortho -PCBs, 2,2’-dichlorobiphenyl (PCB4) and 2,2’,4,4’-tetrachlorobiphenyl (PCB47) can induce ROS production in neutrophil granulocytes through Ca 2+ -dependent activation of NADPH oxidase (Bezdecny et al , 2007; Myhre et al , 2009). Novel data in the current study indicate that blockage of NADPH oxidase activation significantly attenuate PCB153-mediated upregulation of CAM proteins (Figure 5).…”
Section: Discussionsupporting
confidence: 83%
“…To support this notion, our results also indicate an increased superoxide production in PCB153-exposed hCMEC/D3 cells. These observations are supported by recent reports that selected ortho -PCBs, 2,2’-dichlorobiphenyl (PCB4) and 2,2’,4,4’-tetrachlorobiphenyl (PCB47) can induce ROS production in neutrophil granulocytes through Ca 2+ -dependent activation of NADPH oxidase (Bezdecny et al , 2007; Myhre et al , 2009). Novel data in the current study indicate that blockage of NADPH oxidase activation significantly attenuate PCB153-mediated upregulation of CAM proteins (Figure 5).…”
Section: Discussionsupporting
confidence: 83%
“…In this respect, in a recent study, Alegría-Torres et al (Frigo et al, 2004;Kim et al, 2004). Similar findings were found for PCBs (Bezdecny et al, 2007;Glauert et al, 2008;Myhre et al, 2009;Wang et al, 2008). In line with the mechanism proposed by Champion et al (2013), our data showed that the over-expression of AhR was dependent on the TNF induced by DDE and PCB 153.…”
Section: Discussionsupporting
confidence: 91%
“…Those findings indicated that AhR expression in FLSs was stimulated in the presence of TNF, similar to our results here. Taking into account that data and our own, we hypothesize that TNF induced by DDE and PCB 153 (Alegría-Torres et al 2009; Cárdenas-González et al, 2013), likely via an NF-B pathway (Bezdecny et al, 2007;Frigo et al, 2004;Glauert et al, 2008;Kim et al, 2004;Myhre et al, 2009;Wang et al, 2008), was able to induce AhR mRNA expression.…”
Section: Discussionmentioning
confidence: 62%
“…MAPK14 gene expression returned correlations with most of the environmental carcinogens; PCBs, HCB, p,p ′-DDE, and Cd in blood as well as in urine. Upon environmental carcinogenic exposure, reported for PCB-47, MAPK14 functions as a mediator of COX2 gene expression ( Bezdecny et al 2007 ). In turn, COX2 expression is known to be deregulated in certain tumors.…”
Section: Discussionmentioning
confidence: 99%